Description of the sexual generation of Dryocosmus destefanii (Hymenoptera: Cynipidae: Cynipini) and disclosure of its life cycle - Cerasa, Giuliano; Verde, Gabriella Lo; Caleca, Virgilio; Massa, Bruno; Nicholls, James A.; Melika, George (Zootaxa, 2020)
The sexual generation of Dryocosmus destefanii Cerasa & Melika, 2018 that emerges from galls on Q. suber L. in Italy is described for the first time, establishing its heterogonic life cycle. We provide observations on its distribution, illustration of adults and galls and information on its biology as supported by morphological and molecular data. An illustrated identification key to Western Palaearctic Dryocosmus species is also given.